H2O2-preconditioned human adipose-derived stem cells (HC016) increase their resistance to oxidative stress by overexpressing Nrf2 and bioenergetic adaptation - Patricia Garrido-Pascual; Ana Alonso-Varona; Begoña Castro; María Burón; Teodoro Palomares (Stem Cell Research & Therapy, 2020)
Abstract Background Mesenchymal stem cells, including those derived from human adipose tissue (hASCs), are currently being widely investigated for cell therapy. However, when transplanted at the site of injury, the survival and engraftment rates of hASCs are low, mainly due to the harsh microenvironment they encounter, characterized by inflammation and oxidative stress. To overcome these therapeutic limitations, cell preconditioning with low-concentration of hydrogen peroxide (H2O2) has been proposed as a plausible strategy to increase their survival and adaptation to oxidative stress. Nonetheless, the underlying mechanisms of this approach are not yet fully understood. In this study, we analyzed molecular and bioenergetic changes that take place in H2O2 preconditioned hASCs. Methods Long-term exposure to a low concentration of H2O2 was applied to obtain preconditioned hASCs (named HC016), and then, their response to oxidative stress was analyzed. The effect of preconditioning on the expression of Nrf2 and its downstream antioxidant enzymes (HO-1, SOD-1, GPx-1, and CAT), and of NF-κB and its related inflammatory proteins (COX-2 and IL-1β), were examined by Western blot. Finally, the Seahorse XF96 Flux analysis system was used to evaluate the mitochondrial respiration and glycolytic function, along with the total ATP production. Results We found that under oxidative conditions, HC016 cells increased the survival by (i) decreasing intracellular ROS levels through the overexpression of the transcription factor Nrf2 and its related antioxidant enzymes HO-1, SOD-1, GPx-1, and CAT; (ii) reducing the secretion of pro-inflammatory molecules COX-2 and IL-1β through the attenuation of the expression of NF-κB; and (iii) increasing the total ATP production rate through the adaption of their metabolism to meet the energetic demand required to survive. Conclusions H2O2 preconditioning enhances hASC survival under oxidative stress conditions by stimulating their antioxidant response and bioenergetic adaptation. Therefore, this preconditioning strategy might be considered an excellent tool for strengthening the resistance of hASCs to harmful oxidative stress.